2015
DOI: 10.1371/journal.pone.0119144
|View full text |Cite
|
Sign up to set email alerts
|

Polybrominated Diphenyl Ethers (PBDEs) in PM2.5, PM10, TSP and Gas Phase in Office Environment in Shanghai, China: Occurrence and Human Exposure

Abstract: To evaluate risk via inhalation exposure of polybrominated diphenyl ethers (PBDEs) in office environment, thirty-six pairs air samples including PM2.5 (particles with aerodynamic diameter less than 2.5 μm), PM10 (particles with aerodynamic diameter less than 10 μm), total suspended particles (TSP) with matching gas phase were collected in office environment in Shanghai, China. The average concentrations of PM2.5, PM10 and TSP were 20.4, 27.2 and 50.3 μg/m3, respectively. Σ15PBDEs mean concentrations in PM2.5, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 52 publications
(63 reference statements)
3
18
0
Order By: Relevance
“…The PBDEs most commonly observed on indoor particulate matter are BDEs 47, 99, and 100, consistent with the present study [15,43,44]. Studies of indoor particulate matter in Chinese cities, Guangzhou [15] and Shanghai [16,17], observed high particulate matter loadings of BDE-209 (e.g., particulate matter 2.5 mm in diameter concentrations from $10 to >1000 pg/m 3 ). In households in Hong Kong, China [15], and Michigan, USA [43], BDE-209 was not detected in any indoor particulate matter samples.…”
Section: Pbde Congeners Detected In Moudi Samplessupporting
confidence: 90%
See 2 more Smart Citations
“…The PBDEs most commonly observed on indoor particulate matter are BDEs 47, 99, and 100, consistent with the present study [15,43,44]. Studies of indoor particulate matter in Chinese cities, Guangzhou [15] and Shanghai [16,17], observed high particulate matter loadings of BDE-209 (e.g., particulate matter 2.5 mm in diameter concentrations from $10 to >1000 pg/m 3 ). In households in Hong Kong, China [15], and Michigan, USA [43], BDE-209 was not detected in any indoor particulate matter samples.…”
Section: Pbde Congeners Detected In Moudi Samplessupporting
confidence: 90%
“…Exposure to PBDEs via inhalation is low in terms of nanograms per day when compared with other routes of exposure, as reported in PBDE exposure studies . However, effects may also vary by mode of exposure because of human physiology.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…53 Li et al reported that 1.2 pg/kg-BW/day PM 2.5 -bound BDE-209 may be inhaled deep into the lungs and reach the pulmonary alveoli based on research in Shanghai. 9 He et al estimated that the DEDs of the particulate BDE-209 for an adult group ranged from 0.13 to 7.1 pg/kg-BW/day (mean of 1.2 pg/kg-BW/day) at an urban site and from 0.08 to 6.1 pg/kg-BW/day (mean of 0.69 pg/kg-BW/ day) at a rural site near Lake Chaohu, China. 54 In this study, the mean exposure levels of 12 pg/kg-BW/day and 83 pg/kg-BW/day were observed in Guangzhou for BDE-209 and HFRs, indicating high exposure risk.…”
Section: Spatial and Seasonal Variations And Associatedmentioning
confidence: 99%
“…However, the use of deca-BDE in Taiwan has not yet ceased as of present and remains available in the manufacture of its many consumer products (Chao et al, 2014). Due to fine particle deposition, PBDEs bind on particulate matters with aerodynamic diameter less than 2.5 µm, PM 2.5 , respectively (Mandalakis et al, 2009;Li et al, 2015a). Numerous studies have been conducted to investigate PM 2.5 levels due to the possibility of its relatively small particles being deposited more deeply into the lungs causing respiratory ailments and diseases, and other negative health problems Guo et al, 2015a;Li et al, 2015b;Shi et al, 2015;Gao et al, 2016).…”
Section: Introductionmentioning
confidence: 99%